Partial Discharge and Breakdown Strength of Plasma Treated Nanosilica/LDPE Nanocomposites - N. A. Awang; M. H Ahmad; Z. Abdul-Malek; Z. Nawawi; M. A. B. Sidik; M. I. Jambak; Aulia Aulia; E. P. Waldi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Nanocomposites have been actively studied in recent years as an insulating material due to their excellent in electrical, mechanical and thermal properties. Even though, the addition of nanoparticles into polymer matrices showed better performance in relation to partial discharge (PD) and AC breakdown strength tests. However, the introduction of nanoparticles could lead to the formation of agglomeration of the fillers which may nullify the true capabilities of the composites. Therefore, silane coupling agent was introduced for surface functionalization treatment of the nano filler but among the issues associated are toxicity and complexity. In the present study, atmospheric pressure plasma is proposed to enhance the surface functionalization of the nano filler. This proposed method was used to treat the nanosilica (SiO 2 ) surfaces to enhance the interfacial interaction between the host (LDPE) and nano filler. SiO 2 nano filler was added into the LDPE at weight percentages of 1, 3 and 5%. The phase-resolved PD behaviour and Weibull analysis of AC breakdown strength of untreated and plasma-treated LDPE nanocomposites were measured to evaluate the performance of the samples. As results, the plasma treated LDPE nanocomposites experience apparent increments of the PD resistance and AC breakdown strength as compared to the untreated nanocomposites. It is implied that the plasma treatment of nanosilica has contributed to the enhancement of the filler dispersion and eventually reducing the agglomeration.